Deciphering the potential roles of ferroptosis in regulating tumor immunity and tumor immunotherapy - Gu, Xu; Liu, Yu’e; Dai, Xiangpeng; Yang, Yong-Guang; Zhang, Xiaoling (Frontiers in Immunology, 2023)
Cancer immunotherapies, including immune checkpoint inhibition (ICI) and adoptive immune cells therapy, are promising therapeutic strategies. They reactivate the function of immune cells and induce immune responses to attack tumor cells. Although these novel therapies benefited a large amount of cancer patients, many cancer patients have shown fair responses even resistance to cancer immunotherapies, limiting their wide clinical application. Therefore, it is urgent to explore the underlying mechanisms of low response and resistance of cancer immunotherapy to enhance their treatment efficacy. The programmed cell death (PCD) including the ferroptosis, has been demonstrated to play essential roles in antitumor immunity and in regulating the immune response to ICIs. Ferroptosis, a phospholipid peroxidation-mediated, iron-dependent membrane damage, exhibite three critical hallmarks: the oxidation of phospholipids, the lack of lipid peroxide repair capability and the overloading of redox-active iron. Notably, ferroptosis was found to plays important roles in regulating tumor immunity and response to immunotherapy. Therefore, targeting ferroptosis alone or in combination with immunotherapy may provide novel options to promote their antitumor efficacy. However, the effect of ferroptosis on tumor immunity and immunotherapy is affected by the interaction of ferroptosis and cancer cells, immune cells, tumor microenvironment (TME) and others. In this review, we summarized and discussed the critical roles of ferroptosis in regulating antitumor immunity, TME and in the improvement of the therapeutic efficacy of immunotherapy in cancers.